Overexpression of c-erbB2 is a negative prognostic factor in anaplastic astrocytomas - Gulati Michel; Granli Unn S; Ytterhus Borgny; Gulati Sasha; Lydersen Stian; Torp Sverre H (BMC, 2010)
Abstract The epidermal growth factor receptor (EGFR) family, consisting of four tyrosine kinase receptors, c-erbB1-4, seems to be influential in gliomagenesis. The aim of this study was to investigate EGFR gene amplification and expression of c-erbB1-4 receptor proteins in human anaplastic astrocytomas. Formalin-fixed and paraffin-embedded sections from 31 cases were investigated by standard immunohistochemical procedures for expression of c-erbB1-4 receptor proteins using commercial antibodies. EGFR gene amplification was studied by fluorescence in situ hybridization using paraffin-embedded tissues. Two monoclonal antibodies, NCL-EGFR-384 and NCL-EGFR, were used for EGFR detection and they displayed positive immunoreactivity in 97% and 71%, respectively. For c-erbB2 detection three monoclonal antibodies, CB11, 3B5, and 5A2, were applied and they displayed positive immunoreactivity in 45%, 100%, and 52%, respectively. Positive immunostaining for c-erbB3 and c-erbB4 was encountered in 97% and 74%, respectively. The EGFR gene was amplified in 9 out of 31 tumors (29%). After adjusting for age, Karnofsky performance status, and extent of surgical resection, Cox multiple regression analysis with overall survival as the dependent variable revealed that c-erbB2 overexpression detected by the monoclonal antibody clone CB11 was a statistically significant poor prognostic factor (P = 0.004). This study shows the convenience and feasibility of immunohistochemistry when determining the expression of receptor proteins in tissue sections of human astrocytomas. The synchronous overexpression of c-erbB1-4 proteins in anaplastic astrocytomas supports their role in the pathogenesis of these tumors. Further, c-erbB2 overexpression seems to predict aggressive behaviour.